1999
DOI: 10.1002/(sici)1099-0755(199905/06)9:3<279::aid-aqc345>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Bird communities and extended biotic index (EBI) in some tributaries of the Tiber river

Abstract: 1. Riparian birds and macroinvertebrates were studied in five reaches of four tributaries of the Tiber river (Italy). The first aim was to check if stream quality, assessed by extended biotic index (EBI) values, could represent change in the riparian zone, assessed through the bird community. The second was to consider whether stream quality affects the presence of riverine bird species. 2. Stream quality and richness of the riparian bird community were related. In streams with more disturbed macroinvertebrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This is important, in order to understand the impacts of both natural and human factors on avian diversity (Heikkinen et al 2004), as breeding bird communities might reflect the integrity of riparian habitats and often have specific habitat requirements (Sorace et al 1999;Rabac¸a 2004;Rodewald and Bakermans 2006). Essentially, we intend to answer the following question: which environmental variables account for the occurrence of breeding bird species associated with Mediterranean rivers?…”
Section: Introductionmentioning
confidence: 99%
“…This is important, in order to understand the impacts of both natural and human factors on avian diversity (Heikkinen et al 2004), as breeding bird communities might reflect the integrity of riparian habitats and often have specific habitat requirements (Sorace et al 1999;Rabac¸a 2004;Rodewald and Bakermans 2006). Essentially, we intend to answer the following question: which environmental variables account for the occurrence of breeding bird species associated with Mediterranean rivers?…”
Section: Introductionmentioning
confidence: 99%
“…Ormerod et al. , 1986; Sorace, Colombari & Cordiner, 1999; Ormerod, Tyler & Jüttner, 2000). Most importantly, however, there is extensive expertise, both amateur and professional, that can be mobilized to carry out bird monitoring at low cost, and birds attract much popular appeal, for example as ‘headline indicators’ of wider environmental trends (DETR, 1999; Defra, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…But studies on the impact of landuse on air quality and bird diversity are limited. It has been demonstrated that birds serve as indicators of habitat change (Lawton et al 1998;Gregory & Strien, 2010), air quality (Eeva et al, 2000;Eeva et al, 2003) and also water quality (Ormerod & Tyler, 1993;Sorace et al, 1999). We attempted to discuss our results on the impact of changes in landuse patterns on the air quality and bird diversity, particularly to fi nd out whether bird diversity can be used as an indicator of air pollution and landuse changes.…”
Section: Discussionmentioning
confidence: 99%